Comparative situational analysis of comprehensive abortion care in four Southern African countries - Catriona Ida Macleod; Megan Reuvers; John Hunter Reynolds; Antonella Lavelanet; Richard Delate (Global Public Health, 2023)
We report on a comparative situational analysis of comprehensive abortion care (CAC) in Botswana, Eswatini, Lesotho and Namibia. We conducted systematic literature searches and country consultations and used a reparative health justice approach (with four dimensions) for the analysis. The following findings pertain to all four countries, except where indicated. Individual material dimension: pervasive gender-based violence (GBV); unmet need for contraception (15−17%); high HIV prevalence; poor abortion access for rape survivors; fees for sexual and reproductive health (SRH) services (Eswatini). Collective material dimension: no clear national budgeting for SRH; over-reliance on donor funding (Eswatini; Lesotho); no national CAC guidelines or guidance on legal abortion access; poor data collection and management systems; shortage and inequitable distribution of staff; few facilities providing abortion care. Individual symbolic dimension: gender norms justify GBV; stigma attached to both abortion and unwed or early pregnancies. Collective symbolic dimension: policy commitments to reducing unsafe abortion and to post-abortion care, but not to increasing access to legal abortion; inadequate research; contradictions in abortion legislation (Botswana); inadequate staff training in CAC. Political will to ensure CAC within the country’s legislation is required. Reparative health justice comparisons provide a powerful tool for foregrounding necessary policy and practice change.